ANTIOXIDANT TEST OF ETHOSOME KAFFIR LIME LEAVES (Citrus hystrix D.C.) EXTRACT AS SKIN ANTI-AGING WITH DPPH METHOD - Dody Muzuka, Muhammad Okta (Pharmaceutical Journal of Indonesia, 2018)
The main processes causing aging skin can be divided into two types, that are intrinsic and extrinsic. Intrinsic aging is caused by genetic factors and increasing age. Extrinsic aging is caused by environmental factors such as sunlight exposure, air pollution, smoking, and malnutrition. Kaffir lime leaf's extract contains alkaloids, flavonoids (hesperidin and naringenin), terpenoids and phenols that have antioxidant activity. Ethosome is a drug delivery system primarily composed of phospholipids, ethanol, and water as a solvent. The presence of ethanol can decrease temperature transition of stratum corneum lipid and increase fluidity. Method used to determine antioxidant activity as antiaging was Î±-diphenyl-Î²-picrylhydrazyl (DPPH). The ethosome formula was differentiated with three different concentrations of soya lecithin phospholipid with 1,5%; 2,5% and 3%. The kaffir lime leaves ethosome was tested with an organoleptic test, phytochemical screening, pH test, vesicles measurement, morphology test, antioxidant value, and stability test. The extract's yield was obtained 9.85% with ethanol 96% as a solvent and contained phenol, terpenoids, alkaloids and flavonoids on phytochemical screening. The stability test was conducted on day 0, day 15th, and day 30th at 25oC Â± 2oC and relative humidity 60% Â± 5%. The pH test of the ethosome complied the specifications of skin's pH. The vesicles' size of each formula did not comply the specification goal of dermis. Antioxidants test showed that kaffir lime leaves ethosome had a very powerful antioxidant. It could be concluded that kaffir lime leaves extract was a potentially powerful antioxidants.